2017
DOI: 10.2337/db17-0187
|View full text |Cite
|
Sign up to set email alerts
|

A Loss-of-Function Splice Acceptor Variant in IGF2 Is Protective for Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) affects more than 415 million people worldwide, and its costs to the health care system continue to rise. To identify common or rare genetic variation with potential therapeutic implications for T2D, we analyzed and replicated genome-wide protein coding variation in a total of 8,227 individuals with T2D and 12,966 individuals without T2D of Latino descent. We identified a novel genetic variant in the IGF2 gene associated with ∼20% reduced risk for T2D. This variant, which has an allele fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…These findings indicated that interact with IGF2, which played an important role in multiple diseases. [48][49][50] Besides, rs326049 showed significant association with CCDC127 expression, a significantly upregulated gene in lung tumor tissues. Furthermore, co-expression genes with RP11-43F13.3 mainly enriched in DNA replication, homologous recombination, spliceosome pathways.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings indicated that interact with IGF2, which played an important role in multiple diseases. [48][49][50] Besides, rs326049 showed significant association with CCDC127 expression, a significantly upregulated gene in lung tumor tissues. Furthermore, co-expression genes with RP11-43F13.3 mainly enriched in DNA replication, homologous recombination, spliceosome pathways.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the expression of RP11‐43F13.3 was significantly decreased in tumor tissues compared with adjacent normal tissues, indicating that RP11‐43F13.3 might play as a tumor inhibitor. According to lncRNome database, the RP11‐43F13.3 was an antisense and could interact with IGF2 , which played an important role in multiple diseases . Besides, rs326049 showed significant association with CCDC127 expression, a significantly upregulated gene in lung tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recently, a genetic variant in the IGF2 gene associated with about 20% reduced risk for T2D by comparing individuals with and without T2D of Hispanic descent. 51 A loss of function splice acceptor variant in IGF2 is protective for T2D. The absence of this variant was associated with increased incidence of T2D and increased plasma glycated HbA 1c and could be considered as a new therapeutic strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a genetic variant in the IGF2 gene associated with about 20% reduced risk for T2D by comparing individuals with and without T2D of Hispanic descent . A loss of function splice acceptor variant in IGF2 is protective for T2D.…”
Section: Pathophysiology Of T2dmentioning
confidence: 99%
“…Samples collected among isolated populations have facilitated the discovery of a range of relatively common variants with large effect sizes for metabolic phenotypes (Table ). These discoveries include type 2 diabetes susceptibility variants in ABCC8 identified in Pima Indians , and in TBC1D4 identified in Greenlanders , as well as in SLC16A11 and HNF1A identified in the admixed Mexican population , where also a protective type 2 diabetes variant has been identified in IGF2 . Moreover, variants associated with lower lipid levels in APOC3 and DSCAML1 have been identified in an isolated Greek population , variants associated with levels of fatty acids in ACSL6 and CPT1A have been identified in Greenlanders , as well as variants associated with obesity in CREBRF and ADCY3 in Samoans and Greenlanders, respectively , and increased fasting insulin in AKT2 identified in Finns .…”
Section: Genetic Association Studies Of Metabolic Traits In Isolatedmentioning
confidence: 97%